Clinical and pathological correlation in benign breast diseases in women - Kapoor, Bhavuk; Vaid, Parul; Kapoor, Mayank; Kapoor, Bharat B.; Kapoor, Sharda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Benign breast diseases are a common problem presenting in a day to day surgical practice. A combination of three tests i.e. clinical examination, radiological imaging and pathological examination is commonly used to accurately diagnose breast diseases. This study was aimed to know the clinico-pathological correlation in diagnosing benign breast diseases in women. Methods: A study of 30 female patients of benign breast disease was conducted by clinical examination and comparing its accuracy with the pathological findings. Results: The highest incidence of benign breast diseases was in the age group of 30-39 years (33.3%). The most common presenting symptom was lump (53.3%) in the breast. The most common quadrant involved was the upper outer quadrant (60%). Fibroadenoma (53.3%) was the most common lesion in this study. The clinical examination in cases of fibroadenoma had sensitivity and specificity of 87.5 % and 92.8% respectively. In cases of fibrocystic disease, clinical examination had sensitivity and specificity of 85.7 % and 91.3% respectively. Conclusions: Overall clinical breast examination had a sensitivity of 90% and specificity of 98% in this study. Hence, combination of all three diagnostic modalities i.e. clinical, radiological and pathological examination should be used. But in rural areas where radiological and pathological facilities are not available, clinical examination can also give us a fair amount of idea in diagnosing benign breast diseases.